Cambridge Igcse Computer Studies Coursebook. - Leadbetter, Chris; Wainwright, Stewart; University of Cambridge. Local Examinations Syndicate. International Examinations (Cambridgen : Cambridge University Press, 2011)
'Fully covers the Cambridge IGCSE syllabus, offering valuable practical support for students. A new textbook written to match the requirements of the University of Cambridge International Examinations Computer Studies syllabus (0420). Both the theoretical and applied aspects of the course are covered with highly illustrated material. Advice is given on both the compulsory examination, Paper 1, and the two other papers: Paper 2 (coursework) and Paper 3 (alternative to coursework), providing support whichever route is taken. Cambridge IGCSE Computer Studies is designed to develop key skills and subject-based knowledge. Offering valuable practical support for students and written by experienced teachers of Cambridge syllabuses in IGCSE Computer Studies, this new Coursebook includes questions and tasks throughout to reinforce learning. The accompanying CD-ROM provides practice activities for students.'--Publisher's description.
Accompanied by 1 CD-ROM which provides practice activities for students.
'Endorsed by University of Cambridge International Examinations.'--Cover.
'Completely Cambridge - Cambridge resources for Cambridge qualifications.'
Book is accompanied by one computer optical discs entitle'Cambridge Igcse Computer Studies Coursebook' bearing the same call number and available at Bahagian Koleksi Media.
Includes bibliographical references and index.
Keywords: Computer science -- Textbooks